J. Corredor-Matheos, Sin ruido (Pedro Antonio González Moreno) - González Moreno, Pedro Antonio (Estudios Humanísticos. Filología, 2014)
Reseña escrita por Pedro Antonio González Moreno de J. Corredor Mateos, Sin ruido